The Impact of Exposure to Missionaries on the English Language Proficiency and Earnings of Immigrants in the USA - Nicholas Larsen; Barry R. Chiswick (Global Labor Organization (GLO), 2019)
Purpose: The purpose of this paper is to explore how potential exposure to missionary activity impacts both English language proficiency and labor market earnings of male and female immigrants to the United States. Design/Methodology/Approach: This study uses the pooled files of the American Community Survey (2005-09). To estimate the relationship between the missionary activity of both Protestants and Catholics on an immigrant's English language proficiency using a linear probability model and their labor market earnings using the human capital earnings function that is estimated with an ordinary least squares model. Among other relevant variables, the analysis controls for the colonial heritage of the immigrant's country of origin. Findings: Overall, and within colonial heritages, our results indicate that male and female immigrants from countries with a higher concentration of Protestant missionaries tend to exhibit higher levels of English language proficiency and earnings, and those from countries with a greater concentration of Catholic missionaries exhibit lower levels of both, compared to countries with lower concentrations of missionaries. Furthermore, a greater proficiency in English enhances earnings. One of the important implications of the findings in this paper is that a “missionary variable” often used in other studies is too aggregate and may mask important findings because of strikingly different effects of Protestant and Catholic activities and characteristics of the missionaries. Originality/value: This study explores for the first time how, through a missionary concentration variable, potential exposure to missionary activity impacts the English language proficiency and earnings of immigrants.
Keywords: F22; J61; J31; J24; 330; Immigrants; Protestant; Catholic; Missionaries; Earnings; Schooling; English Language; Proficiency; American Community Survey